Pengembangan Pembelajaran Serta Memotivasi Anak Sanggar Pelita di Masa New Normal - Rafly; Tuti Atika (Yayasan Literasi Sains Indonesia, 2022)
This period is a golden age, because children experience very rapid growth and development and cannot be replaced in the future. According to various studies in the field of neurology, it is proven that 50% of children's intelligence is formed within the first 4 years. After children are 8 years old, their brain development reaches 80% and at the age of 18 years reaches 100%. The golden age of child development is a period where all aspects of development can be easily developed through stimulation of appropriate activities in children according to their level of development. Development between children is very different due to internal and external factors. So, every child will experience the same pattern of development but different levels of achievement. one child who is in the Pelita Studio who needs help to increase his interest in learning. The process of providing assistance is carried out on the mini-project of street vendors. 1, by using the casework method through the general intervention stage consisting of Engagement intake Contract, Assessment. Planning / planning. Evaluation and Termination Intervention The focus of the client's problem solving process is to provide motivation and also develop their interest in learning.